2021
DOI: 10.1097/acm.0000000000004480
|View full text |Cite
|
Sign up to set email alerts
|

Reopening a Student-Run Free Clinic During the COVID-19 Pandemic to Provide Care for People Experiencing Homelessness

Abstract: Problem Student-run free clinics (SRFCs) provide health and outreach services to underserved populations while offering medical students opportunities for service and education. Many SRFCs were forced to suspend in-person operations in early 2020 due to the COVID-19 pandemic. Before March 2020, JeffHOPE, the SRFC at Sidney Kimmel Medical College at Thomas Jefferson University, operated an evening clinic at 5 locations throughout Philadelphia each week. Approach JeffHOPE’s r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Here we discuss the development, implementation, and evaluation of an innovative service-learning COVID-19 vaccination program. While there is growing body of literature about medical student contributions to the COVID-19 response [ 5 , 6 , 7 , 8 , 10 , 12 , 15 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], our work is the largest student-lead, community-based vaccination program described to date. It reveals that medical students are effective front-line vaccinators during a global pandemic and can attain a valuable learning experience from this service.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we discuss the development, implementation, and evaluation of an innovative service-learning COVID-19 vaccination program. While there is growing body of literature about medical student contributions to the COVID-19 response [ 5 , 6 , 7 , 8 , 10 , 12 , 15 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], our work is the largest student-lead, community-based vaccination program described to date. It reveals that medical students are effective front-line vaccinators during a global pandemic and can attain a valuable learning experience from this service.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, perhaps, was the accelerated graduation and deployment of senior medical students as new physicians [10,11]. Students have also screened patients for COVID-19 [12], provided telemedicine support [13], worked at patient call centers [14], and facilitated the reopening of student run free-clinics [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primarily, this consists of preventive care and chronic disease management services 9 to those who are uninsured, 10 refugees, 11 or experiencing homelessness. 12 The underserved populations who utilize these clinics may face barriers to telehealth use due to social risk factors, including unmet transportation needs, food insecurity, and housing instability. While telehealth may help overcome transportation barriers, other factors may impede telehealth use in at risk populations including patient poverty level, inadequate access to technology and high-speed internet, as well as limited clinic resources.…”
Section: Introductionmentioning
confidence: 99%
“… 20 Multiple telehealth models have been trialed by SRFCs during the COVID-19 pandemic to maintain access to care among vulnerable populations. 21 - 23 One of these studies reported a decrease in no show rates following the implementation of telehealth, albeit with limited data only spanning 2 months. 21 Here, we provide an in-depth discussion on the implementation of a telehealth model with fully remote visits and the impact on clinic attendance rates.…”
Section: Introductionmentioning
confidence: 99%